Privacy Intensification And Profile Based Search In Web - Mr.Pradeepkumar sahoo, S. Deivanai , (International Journal of Scientific Research and Management (IJSRM), 2015)
Personalized search engine helps to extract useful information from world wide web based on the users area of interest specified in the profile which helps to rank user preferred pages at the first.In this paper when an search item is entered by the user search engine will retrieve the results based on the previous search history of clicked pages which can be obtained by analyzing web logs present in the server and also area of interest specified in the profile. Page ranking is done by content based ranking algorithm which is done based on visitor count, page rank , access time length , feedback (likes/dislikes) ,Term weighing technique , https . Crawlers internet protocol address is monitored regularly by the administrator for providing security and an alert message is sent to crawlers mail if an unauthorized access happens .Location based search is done by automatically locating the latitude and longitude of the user by google apis and all theSearch items containing the addresses are located within the radius and reverse geocoding technique is used to convert Geographic coordinates into addresses